Penerapan Model Kooperatif Tipe Student Team Achievement Division (STAD) Terhadap Hasil Belajar Peserta Didik Di SMP Negeri 2 Nggoa - Kondang, Dorine Devita; Bano, Vidriana Oktoviana; Ndjoeroemana, Yohana Ndjoeroemana (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
The purpose of this study was to describe the application of the Student Team Achievement Division (STAD) cooperative model in improving the learning outcomes of class IX students at SMP Negeri 2 Nggoa. This research is a class action research (CAR) which is carried out in the pre-cycle, cycle I and cycle II activities which consist of planning, action implementation, observation, and reflection. The research subjects were 27 students of class IX. The results showed that the application of the STAD type cooperative model could improve student learning outcomes in science subjects at SMP Negeri 2 Nggoa. Increased cognitive domain, at the stage of the first cycle reached 71% experienced an increase in the second cycle to 88%. Meanwhile, the affective domain in cycle I reached 60% and in cycle II reached 78%. It can be concluded that the application of the Student Team Achievement Division (STAD) cooperative model can improve the learning outcomes of class IX students at SMP Negeri 2 Nggoa on the subject of the human respiratory system. Keywords: learning model, cooperative, STAD, learning outcome